2021
DOI: 10.1038/s41419-021-03794-6
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0026628 promotes the development of colorectal cancer by targeting SP1 to activate the Wnt/β-catenin pathway

Abstract: Circular RNAs (circRNAs) have been reported to play crucial roles in the progression of various cancers, including colorectal cancer (CRC). SP1 (Sp1 transcription factor) is a well-recognized oncogene in CRC and is deemed to trigger the Wnt/β-catenin pathway. The present study was designed to investigate the role of circRNAs which shared the same pre-mRNA with SP1 in CRC cells. We identified that hsa_circ_0026628 (circ_0026628), a circular RNA that originated from SP1 pre-mRNA, was upregulated in CRC cells. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 44 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The results showed that circ_0026628 promoted the proliferation, migration, EMT and dryness of CRC cells. In terms of mechanism, circ_0026628, as the endogenous sponge of miR-346 and FUS, increases the expression of SP1 at the post-transcriptional level, thereby enhancing the interaction between SP1 and β-catenin to activate the Wnt/β-catenin pathway [ 17 ]. The prognosis of locally advanced colorectal cancer (CRC) is currently unsatisfactory.…”
Section: Wnt Pathway-related Biochemical Processmentioning
confidence: 99%
“…The results showed that circ_0026628 promoted the proliferation, migration, EMT and dryness of CRC cells. In terms of mechanism, circ_0026628, as the endogenous sponge of miR-346 and FUS, increases the expression of SP1 at the post-transcriptional level, thereby enhancing the interaction between SP1 and β-catenin to activate the Wnt/β-catenin pathway [ 17 ]. The prognosis of locally advanced colorectal cancer (CRC) is currently unsatisfactory.…”
Section: Wnt Pathway-related Biochemical Processmentioning
confidence: 99%
“…circRNAs form covalently closed loops by back-splicing. This structure makes them highly stable and conserved [ 19 ]. The role of circRNAs in colorectal cancer has received increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA also contributes to the occurrence and development of CRC via acting as a sponge miRNA. CircRNA-102209 upregulates the RIN1 signal via sponging miR-761 [46], circ-0082182 can down-regulate the expression of miR-411 or miR-1205 [47] and circ_0026628 can activate Wnt/β-catenin pathway by enhancing the interaction between SP1 and β-catenin via sponging miR-346 [48], thus promote the proliferation, invasion, and EMT of CRC cells. Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion, and EMT by miR-127-5p/RAB3D axis [49], circ_0085315 can promote cell proliferation, invasion, and migration in colon cancer through miR-1200/MAP3K1 signaling pathway [50], hsa_circ_0007843 can act as a miR-518c-5p sponge to regulate the migration and invasion of colon cancer SW480 cells [51], and circular RNA hsa_circ_0008285 inhibits cell proliferation and migration via the miR-382-5p/PTEN axis.…”
Section: Circrna-associated Cerna Network In Colorectal Cancermentioning
confidence: 99%